Clinical validation of a biopsy‐based six‐gene signature prognostic for aggressive prostate cancer - Agnieszka Krzyzanowska; Debra F. Higgins; Stephen Barron; Tony Loughman; Amanda O'Neill; Katherine M. Sheehan; Chan‐Ju Angel Wang; Bozena Fender; Leah McGuire; Joanna Fay; Anthony O'Grady; Des O'Leary; et al. (BJUI Compass)
Abstract Objectives This study aimed to clinically validate the six‐gene prognostic molecular clinical risk score (MCRS) for the prediction of aggressive prostate cancer in diagnostic biopsy tissue. Methods MCRS was evaluated in prostate biopsy tissue from a Swedish cohort of men with prostate cancer (UPCA, n = 100). The primary outcome of adverse pathology and secondary outcomes of high primary Gleason (≥G4) and high pathological T‐stage (≥T3) were assessed by likelihood ratio statistics and area under the receiver operating characteristic curves from logistic regression models; time to biochemical recurrence was assessed by likelihood ratio statistics and C‐indexes from Cox proportional hazard regression models. Results Biopsy MCRS was significantly prognostic (p < 0.0001) and added significant prognostic value to clinico‐pathological features for adverse pathology, high primary Gleason and high pathological T‐stage (p < 0.0001). MCRS was prognostic for biochemical recurrence and added some, albeit non‐significant, prognostic value to clinical risk stratifiers, which could reflect the low number of recurrence events in the cohort. Conclusion Biopsy‐based MCRS improves risk stratification over standard clinical and pathological information and optimises patient management after diagnosis of prostate cancer.